2021
DOI: 10.1101/2021.03.09.434456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and Structural Basis of Olfactory Sensory Neuron Coalescence by Kirrel Receptors

Abstract: Projections from sensory neurons of olfactory systems coalesce into glomeruli in the brain. The Kirrel receptors are believed to homodimerize via their ectodomains and help separate sensory neuron axons into Kirrel2- or Kirrel3-expressing glomeruli. Here we present the crystal structures of homodimeric Kirrel receptors and show that the closely related Kirrel2 and Kirrel3 have evolved specific sets of polar and hydrophobic interactions, respectively, disallowing heterodimerization while preserving homodimeriza… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…OR-dependent and neural activity-dependent pathways in glomerular segregation converge in the expression pattern of axon sorting molecule. To date, several studies identified multiple activity-dependent axon-sorting molecules that are expressed in OSNs (St John et al, 2002;Cutforth et al, 2003;Kaneko-Goto et al, 2008;Williams et al, 2011;Ihara et al, 2016;Mountoufaris et al, 2017;Vaddadi et al, 2019;Wang et al, 2021;Martinez et al, 2023). The exact number of molecules implicated in this process is still unclear, but a handful of transmembrane proteins are thought to be involved.…”
Section: Molecular Mechanisms Of Or-dependent Glomerular Map Refinementmentioning
confidence: 99%
“…OR-dependent and neural activity-dependent pathways in glomerular segregation converge in the expression pattern of axon sorting molecule. To date, several studies identified multiple activity-dependent axon-sorting molecules that are expressed in OSNs (St John et al, 2002;Cutforth et al, 2003;Kaneko-Goto et al, 2008;Williams et al, 2011;Ihara et al, 2016;Mountoufaris et al, 2017;Vaddadi et al, 2019;Wang et al, 2021;Martinez et al, 2023). The exact number of molecules implicated in this process is still unclear, but a handful of transmembrane proteins are thought to be involved.…”
Section: Molecular Mechanisms Of Or-dependent Glomerular Map Refinementmentioning
confidence: 99%